HE STRUCTURE OF THE FINANCIAL ANALYSIS OF THE FINANCIAL REHABILITATION PROGRAM FOR REAL SECTOR COMPANIES OF THE REPUBLIC OF ARMENIA - Manukyan, Grigor (Crisis Management and Technologies, 2025)
The issue of financial recovery of companies in insolvency conditions is a priority. The insolvency of companies conditioned by unyielding competition, the growth of financial risks of companies, the impact of deep financial and economic crises on the economy and other factors. In order for the company to emerge from the crisis, it is necessary to develop a financial recovery system that will make it possible to quickly diagnose the areas of the "crisis field" and prevent the development and deepening of the crisis situation. There is no document in the legal documents of the Republic of Armenia on the analysis of the financial condition of a company in crisis, which would include the directions of financial analysis and the control process of companies in such a status. Various legislative acts regulate certain parts of the bankruptcy procedure. Taking into account the above, it is necessary to establish a procedure for providing information on the analysis of the financial and economic condition of companies, develop and implement regulations on the analysis of the financial and economic condition, a roadmap for financial recovery and ensure their monitoring.The significance of the article lies in the fact that a systematic and concise presentation of financial analysis in the company's financial recovery plan can be of practical importance for Armenian companies. To present financial analysis as part of the summary section of the financial recovery plan in the event of a company's insolvency. To achieve this goal, the following tasks have been identified: to study the characterization of the restoration of financial stability, to systematize the structure of the financial analysis section, to present the key financial and economic indicators that arbitration managers need to reflect in the debtor's financial recovery plan. The subject of the study is the financial analysis indicators of the financial recovery plan of a crisis company.